Positive law from the Muslim world: jurisprudence, history, practices - Dupret, Baudouin (The law in context series, 2021)
Can the concept of law be indiscriminately extended to times and places in which it did simply not exist? Such an extension is at best useless and at worst misleading. Producing an intelligible jurisprudence of the concept of law means keeping it within the reasonable boundaries of its contemporary common-sense understanding: positive law. Parallel to Western societies in which it firstly emerged, the concept of positive law developed in many places, including countries characterized as Muslim. There, it faced other existing normativities, like customs and the Sharia. This book aims, from the Muslim world's perspective, to clarify the uses of the concept of law and the ways of studying it, to describe some of its historical developments, including the ideas of constitutional law, customary law and forensic evidence, and to describe present-day practices, including reference to law sources, rules and interpretation.